Terminologia Anatomica (TA2), Terminologia Neuroanatomica (TNA) and Terminologia Oroanatomica - Dmitriy, Nikityuk; Sergey, Dydykin; Igor, Zadnipryany; Marina, Kapitonova; Ilia, Kagan; Yuriy, Vasil'ev (2025)
nternational Federation of Anatomical Associations (IFAA) executive committee authorized the translation, adaptation and publication of the Anatomical Terminology (TA2) [followed the official list of 7,113 Latin terms by FIPAT], and Neuroanatomical Terminology (TNA) [followed the official list of 4,399 Latin terms by FIPAT] at the initiative of the President of Russian Anatomical Society (SMSAHE) Prof. Dr. Dmitriy B. Nikityuk, and Vice-President of SMSAHE, Prof. Dr. Sergei S. Dydykin. Oroanatomical Terminology (TOA) was also issued with Russian equivalents and proved to be the 1st edition of the TOA in the world. It includes 2,294 terms related to the head and neck. The Russian anatomical terminologies are not a simple translation of Latin terms, but a historically established system of terms that reflects the contribution of Russian scientists to anatomy. Due to the widespread use of anatomical terminology in the international scientific literature, TA2, TNA and аlso TOA were published in four languages: Latin, Russian and English (UK [Great Britain] and US [United States]). While original version of terminologies includes 7 columns [the first column - the serial number of the term to which all footnotes are referred; six columns {2–7} contain the official Latin term {2}, Latin synonyms {3}, English terms (UK {4} and US {5} and English synonyms (if necessary) {6}. The last column includes related terms, eponyms, and links to endnotes {7}]. In the Russian version another 3 columns are added: {8} - Russian equivalent, {9} - Russian synonym, {10} – Russian eponym. Footnotes are placed in a separate section at the end of each chapter. Terms indicating the location of body parts and organs were described in relation to the anatomical position. Each organ was generally designated by one term, except in cases where a variant of the main term was used to form clinical terms.